Razvoj naracije v slovenskem zgodovinopisju po drugi svetovni vojni in v samostojni Sloveniji - Ratkajec, Hrvoje (Acta Histriae, 2008)
The goal of this article is to illustrate the development of narrative in Slovenian historiography in two different periods (after the Second World War and after Slovenian Independence in 1991). The first thing I had to do was to construct a concept of narrative with which I could analyye a discussion in Slovenian historiography about how history should be written. Based on the studies of work by Jeryy Topolski I tried to combine two different approaches to this question (narrative approach and empirical approach) into one concept of narrative that acknowledges equally the role of the empirical in history (the facts) and the meaning of narrative (the presentation of facts). I applied this concept in an analysis of a discussion between Slovenian historians, finding out what facts about historiography they presented and what their theoretical, ideological and ethical standpoints were. The result of my analysis shows that Slovenian historians after the Second World War positively accepted the Marxist theoretical method of historiography. This began to change after 1980 when historians started to reject this method, saying that it has a negative ideological impact upon a Slovenian historiography. During the period after the Second World War and prior to Slovenian independence there was an obvious change of views regarding the Marxist method. At the beginning it was accepted on the theoretical-historiographical level and on its ideological level and at the end its ideological connotations were rejected and only parts of the theoretical views were welcomed. After Slovenia became an independent country there was a discussion about how Slovenian historiography should accept modern standards in historiography and be a valuable part of a new democratic society. Not many new facts about historiography were presented in that discussion (in comparison to the 1980s when there was a dramatic increase of new information about the Marxist method) but a debate was started about clearing up the old ideological standpoints in historiography and society in general. Thus the discussion in the 1990s and on involved not only historians but also various others.
Keywords: history; ideologija; marksizem; Marxism; Slovenia; Slovenija; zgodovinopisje; zgodovinopisna naracija